Solve for p -17=6p-5

Math
-17=6p-5
Rewrite the equation as 6p-5=-17.
6p-5=-17
Move all terms not containing p to the right side of the equation.
Tap for more steps…
Add 5 to both sides of the equation.
6p=-17+5
Add -17 and 5.
6p=-12
6p=-12
Divide each term by 6 and simplify.
Tap for more steps…
Divide each term in 6p=-12 by 6.
6p6=-126
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6p6=-126
Divide p by 1.
p=-126
p=-126
Divide -12 by 6.
p=-2
p=-2
Solve for p -17=6p-5

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top